Nexus Between Monetary Policy & Liquidity Creation; Study From The Perspective Of Pakistan - Ali, Asad; Mughal , Riffat; Minhas , Asad Ali; Abbas , Qaiser (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
The study investigates whether Pakistan's conventional banks create liquidity in response to monetary policy. The secondary data is gathered from the Thomson Reuter financial data streams. The annual time series data is collected from 2000 to 2021. Conventional banks create liquidity by using liquid liabilities to finance illiquid assets. Ali & Ahmad (2022) estimated the quantity of liquidity created by conventional banks in Pakistan over the past 21 years using the Catfat model developed by Berger and Bouwman (2009). The current study used the estimated amount to examine the impact of monetary policy on liquidity creation by using the simple linear regression econometric model. The outcomes of the study indicate that monetary policy has a significant positive impact on liquidity creation in Pakistan. By regulating the monetary policy rate, the State Bank of Pakistan manages the amount of liquidity that conventional banks create. The decisions made by the State Bank of Pakistan are crucial for the economic development of a country. The future implication of the study is that several bank-specific and industry-specific factors affect liquidity creation, so there is a need to explore the same in different regions of the world.